2019
DOI: 10.1097/brs.0000000000002888
|View full text |Cite
|
Sign up to set email alerts
|

Don’t You Wish You Had Fused to the Pelvis the First Time

Abstract: Study Design. A multicenter retrospective study. Objective. The aim of this study was to compare pelvic obliquity correction and reoperation rate in neuromuscular scoliosis patients who had their pelvis included in a posterior spinal fusion (pelvic fusion, PF) at their index procedure versus revision procedures. Summary of Background Data. There is limited information on outcomes specific to fusing to the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…As such, these authors suggest including the pelvis at the index posterior spinal fusion in this patient population. 8 Although the DSA patients in our study had better scores in several EOSQ-24 domains compared with the DPA patients at their most recent follow-up, it is difficult to know how to interpret these data, as we had incomplete preindex EOSQ-24 scores in the database. Nearly 50% of the complications in the DPA group were medical compared with one third of the complications in the DSA group.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…As such, these authors suggest including the pelvis at the index posterior spinal fusion in this patient population. 8 Although the DSA patients in our study had better scores in several EOSQ-24 domains compared with the DPA patients at their most recent follow-up, it is difficult to know how to interpret these data, as we had incomplete preindex EOSQ-24 scores in the database. Nearly 50% of the complications in the DPA group were medical compared with one third of the complications in the DSA group.…”
Section: Discussionmentioning
confidence: 76%
“…Although we did not find a difference in the complication rate between patients with distal spine or DPAs, increased rates of skin breakdown and infection, implant failure, intraoperative blood loss, longer operative times, and limited mobility have been reported with pelvic instrumentation. 1,7,8,15 Thus, it seems pertinent to determine whether exclusion of the pelvis in spinal deformity procedures is warranted in certain subsets of pediatric NMS patients. Takaso et al 10 retrospectively evaluated patients with flaccid NMS who underwent posterior spinal fusion to L5 using segmental pedicle screw instrumentation.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that revision procedures to extend fusion to the pelvis, when unsatisfactory correction occurs, are often difficult and may be associated with greater morbidity. Nielsen et al 18 demonstrated that extension of fusion to the pelvis in neuromuscular scoliosis was associated with double the reoperation rate (excluding the revision itself) and increased the risk of implant failure, pseudarthrosis, and pain compared with fusion to the pelvis initially.…”
Section: Discussionmentioning
confidence: 99%
“…15,17 Further, when revising patients fused to L5 initially with extensions to the pelvis, there is a higher overall complication rate, risk of implant failure, pseudarthrosis, and revision surgery compared with patients in whom the pelvis was included in the initial operation. 7 In a multicenter retrospective review, Nielsen demonstrated that compared with those with initial pelvic instrumentation, those that were revised to include the pelvis had decreased PO correction (18 vs. 22 degrees). 7 Significantly fewer patients underwent reoperation if treated with fusion to the pelvis at the index procedure (23% vs. 50%), and the revision group had significantly higher rates of implant failure (43% vs. 7%).…”
Section: Consmentioning
confidence: 99%
“…1,2,4,5 Surgical intervention aims to reconstruct a well-aligned, compensated spine over a balanced pelvis while minimizing complications. 2,6,7 Pelvic obliquity (PO) is frequently seen in children with NMS, 8 which may be managed with the extension of the fusion to include the pelvis. Techniques for pelvic instrumentation commonly used at present are iliac and sacral-alar-iliac screws.…”
mentioning
confidence: 99%